Applied and Professional Ethics (KEMANUSIAAN The Asian Journal of Humanities, 2012)
The development of applied ethics in recent decades has had great significance for philosophy and society. In this article, I try to characterise this field of philosophical inquiry. I also discuss the relation of applied ethics to social policy and to professional ethics. In the first part, I address the following questions:(1) What is applied ethics?(2) When and why did applied ethics appear?(3) How do we engage in applied ethics? What are the methods?In the second part of the article, I introduce professional ethics. What is professional ethics, and how can one distinguish professional ethics from applied ethics? I argue that the moral content of professional ethics is a result of professional relations. I also argue that professional ethics best can be understood as a type of virtue ethics.